2014
DOI: 10.2337/db13-1627
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sitagliptin on Glycemia, Incretin Hormones, and Antropyloroduodenal Motility in Response to Intraduodenal Glucose Infusion in Healthy Lean and Obese Humans and Patients With Type 2 Diabetes Treated With or Without Metformin

Abstract: The impact of variations in gastric emptying, which influence the magnitude of glucose-dependent insulinotropic polypeptide (GIP) and glucagon-like peptide 1 (GLP-1) secretion, on glucose lowering by dipeptidyl peptidase-4 (DPP-4) inhibitors is unclear. We evaluated responses to intraduodenal glucose infusion (60 g over 120 min [i.e., 2 kcal/min], a rate that predominantly stimulates GIP but not GLP-1) after sitagliptin versus control in 12 healthy lean, 12 obese, and 12 type 2 diabetic subjects taking metform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(102 citation statements)
references
References 52 publications
6
95
1
Order By: Relevance
“…Moreover, the insulinotropic response to GIP can be partially restored in patients with type 2 diabetes after a period of improved glycemic control (13), including that induced by a DPP-4 inhibitor (14). However, we observed a lack of glucose lowering by sitagliptin in patients with relatively well-controlled type 2 diabetes when glucose was infused intraduodenally at a rate sufficient to stimulate substantial GIP, but minimal GLP-1, secretion (15). Unfortunately, a specific GIP receptor antagonist is not available for use in humans.…”
Section: Dpp-4 Inhibition and The Known Unknowncontrasting
confidence: 41%
“…Moreover, the insulinotropic response to GIP can be partially restored in patients with type 2 diabetes after a period of improved glycemic control (13), including that induced by a DPP-4 inhibitor (14). However, we observed a lack of glucose lowering by sitagliptin in patients with relatively well-controlled type 2 diabetes when glucose was infused intraduodenally at a rate sufficient to stimulate substantial GIP, but minimal GLP-1, secretion (15). Unfortunately, a specific GIP receptor antagonist is not available for use in humans.…”
Section: Dpp-4 Inhibition and The Known Unknowncontrasting
confidence: 41%
“…Although there is recent evidence that about half of the insulinotropic and glucose-lowering effects of sitagliptin are GLP-1 independent (7), we showed that the magnitude of reduction in postprandial glycemia was related directly to the increase in plasma intact GLP-1, consistent with complementary glucoselowering actions of GLP-1 in type 2 diabetes (1). Elevated intact GIP concentrations are likely to contribute less (3,20,21), and GIP administration can even antagonize the glucagonostatic effect of GLP-1 (20). In the current study, the glucagonostatic effect of intact GLP-1 prevailed, and may, to some extent, have contributed Figure 2-Effects of vildagliptin, with or without a whey preload, on plasma glucose (A), gastric half-emptying time (B), plasma insulin (C), plasma glucagon (D), and plasma GIP (E and F for total and intact forms, respectively) and GLP-1 (G and H for total and intact forms, respectively) in response to a high-carbohydrate meal in patients with type 2 diabetes managed by metformin monotherapy (n = 22).…”
Section: Discussionmentioning
confidence: 99%
“…When glucose is administered intraduodenally to mimic the range of physiological rates of gastric emptying (i.e. 1-4 kcal/min), plasma GIP increases linearly with increasing infusion rates, while the GLP-1 response is minimal to glucose infusion at rates between 1 and 2 kcal/min (Wu et al 2014a) but increases substantially in response to infusions of 3 and 4 kcal/min Trahair et al 2012). The latter suggests that a threshold of duodenal glucose delivery of about 2 kcal/min is required to allow for the interaction with L cells located in the relatively distal region of the gut.…”
Section: Regulation Of Incretin Hormone Secretionmentioning
confidence: 99%
“…For example, intravenous infusion of GLP-1 was shown to suppress endogenous GLP-1 production (Toft-Nielsen et al 1999). Furthermore, DPP-4 inhibition, which results in increased plasma concentrations of intact incretins, is associated with reductions in total incretin levels, indicative of overall suppression on incretin secretion (Wu et al 2014a). Conversely, the antagonism of GLP-1 signalling by exendin(9-39) results in an exaggerated peptide YY (PYY) secretion in response to intraduodenal lipid infusion in healthy humans (Steinert et al 2014b), indicating that the feedback regulation is likely to be cell-, but not hormone-, specific, since PYY is synthesised and released from different organelles of L cells (Cho et al 2014).…”
Section: Regulation Of Incretin Hormone Secretionmentioning
confidence: 99%